International Trade of Chilean and Tasmanian Salmon and the Governmental Human Resource Policy enabling its Expansion - Naru, Arslan; Shoaib, Faran (Latin American Journal of Trade Policy, 2019)
International trade policy theorists have repeatedly focused their works on actors developing or implementing policies, rather than the actual policies themselves. Dani Rodrik, Chalmers Johnson and Peter Evans are amongst those renowned international trade and industrialization scholars who dedicated most of their research to human resource development in countries that delivered miraculous economic growth. Chile may be considered one of those miraculous states, in part due to the development of its salmon fishing industry. Tasmania, another southern hemisphere salmon producing region, has also procure a State-guided sectorial development. Both face common attributes and challenges. On one hand, Chile and Tasmania salmon development is highly explained due to the existence of a bureaucratic regime highly supportive of human capital development in the new sector. On the other hand, still both face challenges to find the right balance between profitability and environmental sustenance. Chile has shown record export growth, but it has raised questions on sanitary management; while Tasmania has enforced strict environmental compliance, it has hardly earned anything from exports of Salmon.